Environmental services as an endogenous development strategy: an alternative to deforestation in the state of Acre, Brazil - Steingraber, Ronivaldo; Kanoppa, Ana Paula; Caetano, Janaina Fidelis (Acta Scientiarum. Human and Social Sciences, 2018)
This paper studies the economic actors in the Amazonian deforestation in the State of Acre, Brazil. After a discussion on deforestation causes and its impacts, we propose a development strategy built on forest conservation, as the conservation of the Amazon biome. We conclude that environmental services can be an income-generating alternative for local populations, thereby contributing to the economic development of the State, in accordance with the principles of social equity and environmental protection, especially in new economic sectors, which are related to increased deforestation rate, however, the opportunity costs of these services are higher than those of cattle ranching. To get at this conclusion, it was estimated a linear model by Ordinary Least Squares (OLS) with the annual deforestation rate of the State of Acre between 2000 and 2011 as a dependent variable according to participation of primary sectors; the estimated results indicate the cattle ranching, among others economic activities, as the main cause of deforestation.